Antimicrobial resistance among Escherichia coli that cause childhood community-acquired urinary tract infections in Northern Italy - Caracciolo Alessandra; Bettinelli Alberto; Bonato Claudio; Isimbaldi Clementina; Tagliabue Alessandro; Longoni Laura; Bianchetti Mario G (BMC, 2011)
Abstracts Background Resistance rate of Escherichia coli against antimicrobials that are commonly prescribed in pediatric urinary tract infections is currently a matter of concern. Methods The antimicrobial susceptibility patterns of uropathogenic Escherichia coli strains to the common antibimcrobials ampicillin, cotrimoxazole, coamoxyclav, ceftazidime, ceftriaxone, nitrofurantoin, and gentamycin were determined in 177 children aged from 2 to 36 months. They presented with their first symptomatic community acquired urinary tract infection at the Department of Pediatrics, San Leopoldo Mandic Hospital, Merate-Lecco. Results High rates of ampicillin (inpatients: 50%; outpatients: 52%) resistance were identified. The resistance for cotrimoxazole (inpatients: 22%; outpatients: 15%) and especially coamoxyclav (inpatients: 6%; outpatients: 10%) was less pronounced than that to ampicillin. No resistance or less than 1% of resistance was identified for ceftazidime, ceftriaxone, nitrofurantoin, and gentamycin both in inpatients and in outpatients. Conclusions Italian children affected with a community acquired urinary tract infection are initially managed orally with coamoxyclav or parenterally with ceftriaxone. The results of the present retrospective analysis support this attitude. Parenteral ceftriaxone or an aminoglycoside should be considered for patients on antimicrobial prophylaxis or recently prescribed antimicrobials.